Evaluación de diferentes arreglos en el sistema de siembra maíz-frijol en el oriente antioqueño (1983)
The purpose of this research was to study the net income in the maize - bean, cropping system of eleven arrangement in the oriente antioqueño colombiano, during 1979. The investigation was conducted at Regional Research Center "La Seiva", located in a Colombian cold moderate climate at 2.040 m.s.n.m. with rainfall of 1.500 mm and average temperature of 180 C. The bean genotipes used were ICA Viboral (Climbing habit IV) and Diacol Catio (Stem habit 1) and the corn synthetic variety ICA V 402. A randomized complete block design with three repetition was used. The plots consisted of five rows of 10 meters length for harvesting the three central rows to be harvested. Data of grain yield were taken (kg/ha) to estimate the net income based on selling prices of products at harvest time (corn SCol 14 kg; stem habit I bean SCol 38 and 34 kg and the climbing bean SCol 73 and 67 for similar semester) and the cost by hectare (labor and supplies) for each of the arrangement in the study. The results showed that from the point of view of genetic improvement and the agricultural practices for the cropping system maize-bean it is admisable to study the following arrangements: maize in relay intercropping with climbing beam maize row intercropping with stem habit 1 bean in relay intercropping with climbing habit IV bean and row intercropping with stem habit I bean; monoculture climbing habit IV bean; associated and in relay intercropping maize with climbing habit IV bean and maize row intercropping with stem habit I and in relay intercropping with climbing habit IV bean. Futhemore, it is not recomended, in the cropping system maize-bean, to use the maximum amount of harvests per year (five), due to the relative low incomes and the difficulty to manage the crop, specially pests and diseases control.